ANALISIS SPASIAL RAWAN BANJIR TERHADAP DAMPAK LINGKUNGAN KABUPATEN SIGI PROVINSI SULAWESI TENGAH - Akhbar, Rahmat Kurniadi (Universitas Tadulako, 2019)
Sigi Regency in 2019 has been a flood disaster that submerged several villages around it and brought mud and wood from around the river. The study aims to spatially analyze the spread of flood-prone zones and their causes in Sigi Regency. Spatial analysis method is used in the result data using scoring and weighting methods in five map parameters namely slope, soil type, rainfall, drainage and land cover. From the results of spatial analysis it is known that the distribution of the occurrence of flood-prone zones there are 5 parameters namely not prone to 51.77%, somewhat prone to 28.14%, quite prone to 9.39%, prone to 6.92% and very prone to 3.78%. The main cause of flooding is that changes in land cover each year are increasing and reducing vegetation cover will cause rain water to run off directly to the soil.Keywords: Map parameters, flood-prone zones, changes in land cover, spatial analysis.